International Legal Aspects of Maritime Security in the South China Sea: A Literature Analysis - Leszek KURNICKI (Communications of International Proceedings, 2022)
Legal instruments for providing regional maritime security are discussed in the article. The paper focuses on South China Sea as on one of the most important areas in the World Ocean. There are two key players in this area – the United States and China. The Chinese excessive claims in the Sea provoke some tension in international relations andpose a threat for maritime security there. There are some risks for safety of navigation in the disputed areas of the Sea. Washington tries to contain China, insisting on freedom of navigation as a fundamental principle of international maritime law. The risk of conflicts in the South China Sea and Indo-Pacific region overall has induced the U.S. Administrationto establish a new alliance in the form of the security pact between Australia, the United Kingdom, and the United States (AUKUS) on September 15, 2021. The potential conflicts in the Sea can beprevented through the further development of international maritime law, especially through specifying in detail the legal regime of various maritime zones.
Keywords: AUKUS; freedom of navigation; international law; law of the sea; maritime security; South China Sea